Aluminum-based composite material and preparation method thereof

A ceramic particle reinforced aluminum-based composite material with a fiber cloth friction layer addresses the challenge of balancing mechanical, friction, and electrical properties, offering improved hardness, wear resistance, and conductivity for high-strength applications.

CN119239074AActive Publication Date: 2025-01-03HENAN UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411386925.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing aluminum-based composite materials struggle to simultaneously achieve good mechanical properties, friction properties, and electrical conductivity, particularly in applications requiring high strength, wear resistance, and efficient current transmission.

Method used

A ceramic particle reinforced aluminum-based composite material with a friction layer composed of an aluminum matrix and fiber cloth, where the fiber cloth is infiltrated and aligned with the friction direction, enhancing mechanical strength, wear resistance, and electrical conductivity.

Benefits of technology

The composite material achieves improved hardness, compressive strength, wear resistance, and electrical conductivity, maintaining a lightweight structure suitable for high-strength, high-temperature environments with enhanced corrosion resistance and current-carrying tribological properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of aluminum-based alloys, and particularly relates to an aluminum-based composite material and a preparation method thereof. The aluminum-based composite material comprises a ceramic particle reinforced aluminum-based composite material and a friction layer compounded on the surface of the ceramic particle reinforced aluminum-based composite material, the friction layer comprises an aluminum matrix, and at least two layers of fiber cloth are compounded in the aluminum matrix in the thickness direction of the aluminum matrix. The spreading direction of the fiber cloth is consistent with the friction bearing direction of the friction layer, and the fiber cloth is infiltrated by the aluminum base body to form an integrated structure. The friction layer is arranged, ceramic particles can greatly improve the hardness, strength and abrasion resistance of the aluminum-based material, the ceramic particle reinforced aluminum-based composite material and the fiber cloth layer synergistically improve the pressure resistance, structural stability, high-temperature stability and durability of the aluminum-based material, and the friction layer enhances the corrosion resistance and current-carrying friction performance of the material. The method is suitable for application fields requiring high-strength-to-weight ratio, wear resistance, corrosion resistance, good thermal stability and electrical conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum-based alloys, and in particular to an aluminum-based composite material and a preparation method thereof. Background Art

[0002] As a typical lightweight and high-strength material, aluminum-based composites have the advantages of light weight, good thermal conductivity, thermal fatigue resistance and electrical conductivity. They occupy a key position in the research of metal-based composites and are widely used in the automotive industry, aerospace and other fields. In recent years, particle-reinforced aluminum-based composites have been rapidly developed. This material achieves different mechanical and performance properties of aluminum-based materials by changing the type, content and size of the reinforcing particles. The reinforcing particles introduced into aluminum-based composites mainly include ceramic particles, carbon nanotubes, nanowires and graphene.

[0003] However, for the friction service environment of aluminum-based composite materials, they must not only have good mechanical properties to resist plastic deformation, but also have good tribological properties and electrical conductivity. For example, in the field of electromagnetic transmission, the aluminum armature and the guide rail produce relative motion under charged conditions, so the aluminum armature is required to have not only good mechanical and friction resistance properties, but also good electrical conductivity of the aluminum armature is the key to ensure efficient and stable service of the system due to the requirement of large current transmission. Summary of the invention

[0004] The purpose of the present invention is to provide an aluminum-based composite material to solve the problem that the prior art cannot simultaneously take into account the mechanical properties, friction properties and electrical conductivity of the aluminum-based composite material.

[0005] The second object of the present invention is to provide a method for preparing an aluminum-based composite material to solve the problem that the prior art cannot simultaneously take into account the mechanical properties, friction properties and conductive properties of the aluminum-based composite material.

[0006] In order to solve the above technical problems, the technical solution of the aluminum-based composite material of the present invention is: An aluminum-based composite material comprises a ceramic particle reinforced aluminum-based composite material and a friction layer composited on the surface of the ceramic particle reinforced aluminum-based composite material, wherein the friction layer comprises an aluminum matrix, wherein at least two layers of fiber cloth are composited in the aluminum matrix along the thickness direction of the aluminum matrix, wherein the spreading direction of the fiber cloth is consistent with the direction in which the friction layer is subjected to friction, and the fiber cloth is infiltrated and penetrated by the aluminum matrix to form an integrated structure.

[0007] The present invention is an improvement on the prior art, and provides an aluminum-based composite material, wherein a friction layer is arranged on the surface of the ceramic particle reinforced aluminum-based composite material, the friction layer includes an aluminum matrix, and at least two layers of fiber cloth are compounded in the aluminum matrix along the thickness direction of the aluminum matrix, so as to form an aluminum-based composite material with a ceramic particle reinforced aluminum-based composite material inside and a continuous fiber-coated aluminum-based composite material outside, or an aluminum-based composite material with a ceramic particle reinforced aluminum-based composite material at the bottom and a continuous fiber-coated aluminum-based composite material at the top. Among them, the ceramic particles with high hardness, high strength, good thermal stability and chemical stability can greatly improve the hardness, strength and wear resistance of the aluminum-based material, the ceramic particle reinforced aluminum-based composite material and the fiber cloth layer synergistically improve the compressive strength and structural stability of the aluminum-based material, as well as the stability and durability in a high temperature environment, the friction layer enhances the corrosion resistance and wear resistance of the material and improves its current-carrying tribological performance, while maintaining its lightweight characteristics, and taking into account the mechanical properties, friction properties and electrical conductivity of the aluminum-based composite material.

[0008] In order to further improve the wear resistance and tribological properties of the aluminum-based material, preferably, the outermost side of the friction layer is a fiber cloth infiltrated with aluminum, and the thickness of the friction layer is 2-3 mm.

[0009] In order to further improve the strength and hardness of the aluminum-based material, preferably, the ceramic particle reinforced aluminum-based composite material consists of an aluminum alloy matrix and ceramic particles with a volume fraction of 5-10%.

[0010] In order to further improve the strength and hardness of the aluminum-based material, preferably, the aluminum alloy matrix is ​​selected from one or more of aluminum alloy A356, aluminum alloy 2024, aluminum alloy 6063 and aluminum alloy 7075, and the ceramic particles are selected from SiC, Al 2 O 3 and TiB 2 One or more of .

[0011] In order to further improve the friction and wear resistance and compression resistance of the surface of the aluminum-based material, preferably, the fiber cloth is carbon fiber cloth.

[0012] The technical solution of the preparation method of the aluminum-based composite material of the present invention is: A method for preparing an aluminum-based composite material comprises the following steps: alternately laying aluminum plates and fiber cloths on the surface of the ceramic particle reinforced aluminum-based composite material, with the aluminum plates being the outermost after the laying, followed by pressure sintering, and then removing the outermost aluminum layer to expose the fiber cloth.

[0013] The preparation method of the aluminum-based composite material of the present invention comprises the steps of alternately laying aluminum plates and fiber cloths on the surface of the ceramic particle-reinforced aluminum-based composite material and then performing pressure sintering. The ceramic particles with high hardness, high strength, good thermal stability and chemical stability can greatly improve the hardness, strength and wear resistance of the aluminum-based material. The ceramic particles and the fiber cloth layer synergistically improve the compressive strength and structural stability of the aluminum-based material as well as its stability and durability in high temperature environments. The friction layer enhances the corrosion resistance and wear resistance of the material and improves its current-carrying tribological properties while maintaining its lightweight characteristics. The preparation method of the present invention has a simple process and high production efficiency.

[0014] In order to further improve the metallurgical bonding strength of sintering, preferably, the temperature of the pressure sintering is 630-650° C., the pressure of the pressure sintering is 15-20 MPa, and the time of the pressure sintering is 2-3 h.

[0015] In order to further improve the uniformity of the structure of the ceramic particle reinforced aluminum-based composite material, preferably, the ceramic particle reinforced aluminum-based composite material is obtained by mixing aluminum alloy powder and ceramic particles, forming and sintering, the sintering temperature is 500-600°C, and the sintering time is 5-10 minutes. The ceramic particle reinforced aluminum-based composite material is prepared by powder metallurgy process.

[0016] In order to further avoid cracks and pores after sintering, preferably, cooling is performed after sintering, and cooling is performed after pressure sintering, and the cooling rate during cooling is 10-15°C / min. Machining and surface treatment are performed after cooling to meet the requirements of specific size and surface finish.

[0017] In order to further regulate the coordinated improvement of the electrical conductivity and mechanical properties of the aluminum-based composite material, preferably, the number of the aluminum plates and fiber cloths laid does not exceed 5, and the thickness of the aluminum plate is 1-1.2 mm. DETAILED DESCRIPTION

[0018] The technical concept of the aluminum-based composite material of the present invention is as follows: The aluminum-based composite material provided by the present invention utilizes an aluminum matrix formed by infiltration and penetration to form an integral structure and a fiber cloth composited therein as a friction layer on the surface of the matrix. Without affecting the hardness, strength and wear resistance of the matrix, the reinforcing particles inside the matrix and the fiber cloth in the friction layer synergistically improve the compressive resistance and structural stability of the aluminum-based material as well as the stability and durability in a high temperature environment. The presence of the fiber cloth takes into account the corrosion resistance, wear resistance and current-carrying tribological properties of the material while maintaining its lightweight characteristics. It can simultaneously take into account the mechanical properties, friction properties and electrical conductivity of the aluminum-based composite material, and is very suitable for application fields requiring a high strength-to-weight ratio, wear resistance and corrosion resistance, good thermal stability and electrical conductivity.

[0019] The embodiments of the present invention are further described below in conjunction with specific examples. The chemical reagents involved in the following examples are all commercially available conventional products unless otherwise specified.

[0020] 1. Specific embodiments of the aluminum-based composite material of the present invention Example 1 The aluminum-based composite material of this embodiment includes TiB 2 Particle reinforced aluminum matrix composites and composites in TiB 2 The friction layer on the surface of the particle-reinforced aluminum matrix composite material is composed of an aluminum matrix and five carbon fiber cloth layers arranged along the thickness direction of the aluminum matrix inside the aluminum matrix. The five carbon fiber cloth layers are infiltrated by the aluminum matrix to form an integrated structure. The outermost layer of the friction layer is a carbon fiber cloth infiltrated with aluminum. The thickness of the friction layer is 3 mm, of which the TiB in the lower layer is 2 The particle reinforced aluminum matrix composite material is composed of aluminum alloy 6063 matrix and TiB dispersed in the matrix with a volume fraction of 5%. 2 Particle composition.

[0021] Example 2 The aluminum-based composite material of this embodiment includes TiB 2 Particle reinforced aluminum matrix composites and composites in TiB 2 The friction layer on the surface of the particle-reinforced aluminum matrix composite material is composed of an aluminum matrix and five carbon fiber cloth layers arranged along the thickness direction of the aluminum matrix inside the aluminum matrix. The five carbon fiber cloth layers are infiltrated by the aluminum matrix to form an integrated structure. The outermost layer of the friction layer is a carbon fiber cloth infiltrated with aluminum. The thickness of the friction layer is 3 mm, of which the TiB in the lower layer is 2 The particle reinforced aluminum matrix composite material is composed of aluminum alloy 6063 matrix and TiB dispersed in the matrix with a volume fraction of 10%. 2 Particle composition.

[0022] Example 3 The aluminum-based composite material of this embodiment includes TiB 2 Particle reinforced aluminum matrix composites and composites in TiB 2 The friction layer on the surface of the particle-reinforced aluminum matrix composite material is composed of an aluminum matrix and five carbon fiber cloth layers arranged along the thickness direction of the aluminum matrix inside the aluminum matrix. The five carbon fiber cloth layers are infiltrated by the aluminum matrix to form an integrated structure. The outermost layer of the friction layer is a carbon fiber cloth infiltrated with aluminum. The thickness of the friction layer is 2 mm, of which the TiB in the lower layer is 2 The particle reinforced aluminum matrix composite material is composed of aluminum alloy 6063 matrix and TiB dispersed in the matrix with a volume fraction of 5%. 2 Particle composition.

[0023] 2. Specific embodiments of the method for preparing the aluminum-based composite material of the present invention Example 4 The preparation method of the aluminum-based composite material of this embodiment is as follows: 1) Ceramic particle reinforced aluminum matrix composites 6063 aluminum alloy powder is used, with an average particle size of 6-9μm, and the main alloy components are Al, Mg, and Si; ceramic particles are TiB 2 The particles have an average particle size of 2 μm and are irregular polygonal in shape. The 6063 aluminum alloy powder and TiB 2 The particles (100 mesh, volume fraction 5 vol.%) were uniformly dispersed: the weighed 6063 aluminum alloy powder, TiB 2 The particles are loaded into the tank in turn, and agate balls are loaded into the tank in advance to help the 6063 aluminum alloy powder and TiB 2 The particles are evenly mixed to obtain a composite powder. The mass ratio of large, medium and small agate balls added is 1:3:6, the ball-to-material ratio is 1:1, the powder mixing rotation speed is 45 r / min, and the mixing time is 8 h.

[0024] The composite material was prepared by spark plasma (SPS) sintering and hot extrusion process: the composite powder obtained above was placed in a graphite mold with a diameter of φ40 mm, and the mold was separated from the powder by graphite paper to facilitate demolding after sintering. The mold was placed in the sintering chamber of a FHP-828 rapid hot pressing sintering furnace. When the vacuum degree was evacuated to 1.6 Pa, the set heating program was turned on for sintering. The SPS sintering had a heating rate of 100 ℃ / min and a temperature of 500 ℃. The temperature was kept at 30 MPa for 5 min and cooled with the furnace after the end of the heat preservation. When the temperature in the furnace dropped to about 100 ℃, the mold was taken out for cooling and demolding to obtain a TiB with a diameter of φ40 mm. 2 Particle reinforced aluminum matrix composites.

[0025] 2) Aluminum-based composite materials Five 1 mm thin aluminum plates (40 mm × 40 mm) and five carbon fiber cloths (T700, 12K, 40 × 40 mm) were laid alternately to form a multilayer structure. The multilayer structure was placed on the TiB 2 The surface of the particle-reinforced aluminum matrix composite material is such that the aluminum plate is located away from the TiB 2 The outermost layer of the particle reinforced composite material surface was pressurized and sintered at 630℃ (near the melting point of 6063 aluminum alloy) for 2h under 15 MPa. The thin aluminum plate melted and penetrated into the gaps between the carbon fibers to form a surface friction layer. 2The particle reinforced aluminum-based composite material forms a good metallurgical bond, and after the pressure sintering is completed, it is cooled to room temperature at a cooling rate of 10°C / min, and machined about 0.3 mm to expose the fiber cloth to obtain an aluminum-based composite material, which is the aluminum-based composite material of Example 1.

[0026] Example 5 The preparation method of the aluminum-based composite material of this embodiment is as follows: 1) Ceramic particle reinforced aluminum matrix composites 6063 aluminum alloy powder is used, with an average particle size of 6-9μm, and the main alloy components are Al, Mg, and Si; ceramic particles are TiB 2 The particles have an average particle size of 2 μm and are irregular polygonal in shape. The 6063 aluminum alloy powder and TiB 2 The particles (100 mesh, volume fraction 10 vol.%) were uniformly dispersed: the weighed 6063 aluminum alloy powder, TiB 2 The particles are loaded into the tank in turn, and agate balls are loaded into the tank in advance to help the 6063 aluminum alloy powder and TiB 2 The particles are evenly mixed to obtain a composite powder. The mass ratio of large, medium and small agate balls added is 1:3:6, the ball-to-material ratio is 1:1, the powder mixing rotation speed is 45 r / min, and the mixing time is 8 h.

[0027] The composite material was prepared by spark plasma (SPS) sintering and hot extrusion process: the composite powder obtained above was placed in a graphite mold with a diameter of φ40 mm, and the mold was separated from the powder by graphite paper to facilitate demolding after sintering. The mold was placed in the sintering chamber of a FHP-828 rapid hot pressing sintering furnace. When the vacuum degree was evacuated to 1.6 Pa, the set heating program was turned on for sintering. The SPS sintering had a heating rate of 100 ℃ / min and a temperature of 500 ℃. The temperature was kept at 30 MPa for 5 min and cooled with the furnace after the end of the heat preservation. When the temperature in the furnace dropped to about 100 ℃, the mold was taken out for cooling and demolding to obtain a TiB with a diameter of φ40 mm. 2 Particle reinforced aluminum matrix composites.

[0028] 2) Aluminum-based composite materials Five 1 mm thin aluminum plates (40 mm × 40 mm) and five carbon fiber cloths (T700, 12K, 40 × 40 mm) were laid alternately to form a multilayer structure. The multilayer structure was placed on the TiB 2 The surface of the particle-reinforced aluminum matrix composite material is such that the aluminum plate is located away from the TiB 2The outermost layer of the particle reinforced composite material surface was pressurized and sintered at 630℃ (near the melting point of 6063 aluminum alloy) for 2h under 15 MPa. The thin aluminum plate melted and penetrated into the gaps between the carbon fibers to form a surface friction layer. 2 The particle reinforced aluminum-based composite material forms a good metallurgical bond, and after the pressure sintering is completed, it is cooled to room temperature at a cooling rate of 10°C / min, and machined to expose the fiber cloth by about 0.3 mm to obtain an aluminum-based composite material, which is the aluminum-based composite material of Example 2.

[0029] Example 6 The preparation method of the aluminum-based composite material of this embodiment is as follows: 1) Ceramic particle reinforced aluminum matrix composites 6063 aluminum alloy powder is used, with an average particle size of 6-9μm, and the main alloy components are Al, Mg, and Si; ceramic particles are TiB 2 The particles have an average particle size of 2 μm and are irregular polygonal in shape. The 6063 aluminum alloy powder and TiB 2 The particles (100 mesh, volume fraction 5 vol.%) were uniformly dispersed: the weighed 6063 aluminum alloy powder, TiB 2 The particles are loaded into the tank in turn, and agate balls are loaded into the tank in advance to help the 6063 aluminum alloy powder and TiB 2 The particles are evenly mixed to obtain a composite powder. The mass ratio of large, medium and small agate balls added is 1:3:6, the ball-to-material ratio is 1:1, the powder mixing rotation speed is 45 r / min, and the mixing time is 8 h.

[0030] The composite material was prepared by spark plasma (SPS) sintering and hot extrusion process: the composite powder obtained above was placed in a graphite mold with a diameter of φ40 mm, and the mold was separated from the powder by graphite paper to facilitate demolding after sintering. The mold was placed in the sintering chamber of a FHP-828 rapid hot pressing sintering furnace. When the vacuum degree was evacuated to 1.6 Pa, the set heating program was turned on for sintering. The SPS sintering had a heating rate of 100 ℃ / min and a temperature of 500 ℃. The temperature was kept at 30 MPa for 5 min and cooled with the furnace after the end of the heat preservation. When the temperature in the furnace dropped to about 100 ℃, the mold was taken out for cooling and demolding to obtain a TiB with a diameter of φ40 mm. 2 Particle reinforced aluminum matrix composites.

[0031] 2) Aluminum-based composite materials Three 1 mm thin aluminum plates (40 mm × 40 mm) and three carbon fiber cloths (T700, 12K, 40 × 40 mm) were laid alternately to form a multilayer structure. The multilayer structure was placed on the TiB 2The surface of the particle-reinforced aluminum matrix composite material is such that the aluminum plate is located away from the TiB 2 The outermost layer of the particle reinforced composite material surface was pressurized and sintered at 630℃ (near the melting point of 6063 aluminum alloy) for 2h under 15 MPa. The thin aluminum plate melted and penetrated into the gaps between the carbon fibers to form a surface friction layer. 2 The particle reinforced aluminum-based composite material forms a good metallurgical bond. After the pressure sintering is completed, it is cooled to room temperature at a cooling rate of 10°C / min. It is machined by about 0.3 mm to expose the fiber cloth, and the obtained aluminum-based composite material is the aluminum-based composite material of Example 3.

[0032] 3. Comparison Comparative Example 1 The aluminum-based composite material of this comparative example is 6063 aluminum alloy. The specific preparation method is: directly select 6063 aluminum alloy powder (average particle size is 6-9μm, main alloy components are Al, Mg, Si) for SPS sintering, the heating rate is 100℃ / min, the sintering temperature is 500℃, and it is kept warm for 5 min at 30 MPa. After the insulation is completed, it is cooled with the furnace. When the temperature in the furnace drops to 100℃, the mold is taken out for cooling and demolding to obtain a 6063 aluminum alloy with a diameter of φ40 mm.

[0033] Comparative Example 2 The aluminum-based composite material of this comparative example is an integral carbon fiber reinforced aluminum-based composite material, and the preparation method directly adopts the stacking sintering infiltration method, specifically: 20 1 mm thin aluminum plates (40 mm×40 mm) and 20 carbon fiber cloths (T700, 12K, 40×40 mm) are alternately laid to form a multilayer structure, and the multilayer structure is pressurized and sintered at 630°C (near the melting point of 6063 aluminum alloy) at 15 MPa for 2 h, and cooled to room temperature at a cooling rate of 10°C / min to obtain an integral carbon fiber reinforced aluminum-based composite material.

[0034] IV. Experimental Examples Experimental Example 1 This experimental example tests the mechanical properties, electrical conductivity, and current-carrying friction properties of the aluminum-based composite materials of the embodiments and comparative examples, wherein the mechanical properties are measured using a Brinell hardness tester to measure the hardness of the aluminum-based composite materials, and the electrical conductivity is measured using an eddy current electrical conductivity tester to test the electrical conductivity (%IACS) of the aluminum-based composite materials, wherein the contact of the tester is in contact with the friction layer of the aluminum-based composite materials to test the electrical conductivity, and the current-carrying friction properties are measured using a pin-disc current-carrying friction tester, and the mating material is chromium-zirconium-copper (brand: C18150). The test results are shown in Table 1.

[0035] The current-carrying efficiency mainly refers to the current transmission capacity of the current-carrying friction pair during the current-carrying friction and wear process. It mainly measures the ability of the friction pair to dynamically accept current. It is the ratio of the average value of the current actually passing through the friction pair during the friction process to the current set at rest, and is calculated by the following formula: Where: ε represents the current carrying efficiency of the friction sample (%); I represents the average value of the actual current passing through the test process (A); I 0 Indicates the set current (A) when stationary.

[0036] Table 1 Performance test results of aluminum matrix composites It can be seen from Table 1 that, relative to the pure aluminum matrix (Comparative Example 1), the aluminum-based composite material provided by the present invention has an increased hardness while significantly reducing the friction coefficient and improving the current-carrying efficiency, indicating that the friction resistance of the aluminum-based composite material of the present invention is greatly improved; compared to the overall carbon fiber / aluminum composite material (Comparative Example 2), the aluminum-based composite material provided by the present invention has a greatly improved conductivity and improved current-carrying efficiency without having much effect on the hardness and friction coefficient, taking into account the mechanical properties, friction properties and conductive properties of the aluminum-based composite material.

[0037] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An aluminum-based composite material, characterized in that: It includes a ceramic particle reinforced aluminum-based composite material and a friction layer composited on the surface of the ceramic particle reinforced aluminum-based composite material, the friction layer includes an aluminum matrix, at least two layers of fiber cloth are composited in the aluminum matrix along the thickness direction of the aluminum matrix, the spreading direction of the fiber cloth is consistent with the direction in which the friction layer is subjected to friction, and the fiber cloth is infiltrated and penetrated by the aluminum matrix to form an integrated structure.

2. The aluminum-based composite material according to claim 1, characterized in that: The outermost side of the friction layer is a fiber cloth infiltrated with aluminum, and the thickness of the friction layer is 2-3 mm.

3. The aluminum-based composite material according to claim 1, characterized in that: The ceramic particle reinforced aluminum-based composite material consists of an aluminum alloy matrix and ceramic particles with a volume fraction of 5-10%.

4. The aluminum-based composite material according to claim 3, characterized in that: The aluminum alloy matrix is ​​selected from one or more of aluminum alloy A356, aluminum alloy 2024, aluminum alloy 6063 and aluminum alloy 7075, and the ceramic particles are selected from one or more of SiC, Al2O3 and TiB2.

5. The aluminum-based composite material according to claim 1, characterized in that: The fiber cloth is carbon fiber cloth.

6. A method for preparing the aluminum-based composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Aluminum plates and fiber cloths are alternately laid on the surface of the ceramic particle reinforced aluminum matrix composite material. After the laying is completed, the aluminum plate is on the outermost side. Then, pressure sintering is performed, and then the outermost aluminum layer is removed to expose the fiber cloth.

7. The method for preparing the aluminum-based composite material according to claim 6, characterized in that: The pressure sintering temperature is 630-650° C., the pressure of the pressure sintering is 15-20 MPa, and the pressure sintering time is 2-3 hours.

8. The method for preparing the aluminum-based composite material according to claim 6, characterized in that: The ceramic particle reinforced aluminum-based composite material is obtained by mixing aluminum alloy powder and ceramic particles, forming and sintering the mixture. The sintering temperature is 500-600° C. and the sintering time is 5-10 minutes.

9. The method for preparing the aluminum-based composite material according to claim 6, characterized in that: After the pressure sintering is completed, cooling is performed, and the cooling rate during the cooling is 10-15°C / min.

10. The method for preparing the aluminum-based composite material according to claim 6, characterized in that: The number of the aluminum plates and fiber cloth laid does not exceed 5, and the thickness of the aluminum plates is 1-1.2 mm.

Citation Information

Patent Citations

  • Silicon carbide fiber reinforced aluminum base composite material and preparation method thereof

    CN110396652A

  • Carbon fiber reinforced aluminum alloy laminate component forming process and forming die

    CN113787734A

  • Preparation method of continuous ceramic fiber reinforced aluminum-based composite material

    CN114921734A

  • PRODUCTION OF MATERIALS

    DK336689D0

  • heat-resistant panels

    NO975108A